EPISTEMOLOGY QUESTION: RELATIONSHIPS OF SENSING, REASON, INTUITION, AND REVELATION IN ISLAMIC SCIENTIFIC BUILDINGS - Supriatin, Supriatin; Salminawati, Salminawati; Usiono, Usiono (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The purpose of this research is to find out and analyze the relationship between sense, reason, intuition, and revelation in the building of Islamic scholarship. The method used in this study is in the form of pure literature with the techniques used in collecting data based on documentation through written heritage evidence such as writings or manuscripts, archives, books on opinions, theories, concepts as well as propositions, and related laws. with the formulation of the study problem. Based on this research it was found that Islamic Education must be built and developed based on epistemology to realize quality and competitive Islamic education so that it can compete and excel. The source of knowledge essentially comes from the only one, namely Allah SWT, then it is developed through the verses of qauliyyah (Revelation) and kauniyyah (nature and His creatures) which can be studied and developed by humans through the five senses and reason, intuition (instinct) and heart to acquire knowledge. And Islamic scholarship is built from these sources, namely revelation, senses, reason, and heart (intuition).